Mining in Arctic and Non-Arctic Regions: A Socioeconomic Assessment - Anders Frederiksen; Maja Due Kadenic (Institute for the Study of Labor (IZA), 2016)
In this paper, we study how mines change local societies in the Nordic countries with a particular focus on the Arctic region. Our study is based on register data at the municipality level from Norway, Sweden, and Finland for the period 1986 to 2013. The applied econometric model allows for identification of the total socioeconomic effects that occur throughout the mine's life cycle. We find positive effects on local employment and reductions in unemployment and the number of people outside the labor force when a mine is opening up. We also detect significant shifts in the industry structure in the period around a mine opening and we find that mines attract young people and reduce crime rates. We do not find any effects on the local population size, the gender or education compositions, or fertility rates.
Keywords: J2; J15; O12; 330; mining; Arctic; socioeconomic effects; resource development; Nordic countries